Cabazitaxel for metastatic castration-resistant prostate cancer: safety data from the Spanish expanded access program. (September 2014) - Castellano, Daniel; Antón Aparicio, Luis M; Esteban, Emilio; Sánchez-Hernández, Alfredo; Germà, Jose Ramón; Batista, Norberto; Maroto, Pablo; Pérez-Valderrama, Begoña; Luque, Raquel; Méndez-Vidal, María José
<x xml:space="preserve">Abstract</x> Background: Based on the TROPIC study results, cabazitaxel was approved for the management of metastatic castration-resistant prostate cancer (mCRPC) progressing on or after docetaxel. Methods: This multi-centre program provided early access to cabazitaxel to patients with mCRPC before its commercialization. Safety data from 153 Spanish patients receiving cabazitaxel 25 mg/m2 i.v. Q3W, plus oral prednisone/prednisolone 10 mg daily, are reported. Results: Median age of patients was 70 years (26.8% ≥ 75 years), 94.1 and 26.8% had bone and visceral metastasis, respectively. Most had an Eastern Cooperative Oncology Group ≤ 1 (88.9%) and had received a median of 8.0 cycles of last docetaxel treatment. The median of cabazitaxel cycles and cumulative dose were 6.0 (Interquartile range [IQR]: 4.0; 8.0) and 148.9 (IQR: 98.2; 201.4) mg/m2, respectively. Adverse events (AEs) possibly related to cabazitaxel occurred in 143 (93.5%) patients. The most frequent grade ≥ 3 AEs were neutropenia (n = 25, 16.3%) and asthenia (n = 17, 11.1%). Febrile neutropenia and grade ≥ 3 diarrhea occurred in 5.2% of the patients each. There were five (3.3%) possibly treatment-related deaths, mainly infection-related. G-CSFs were used in 114 (74.5%) patients, generally as prophylaxis (n = 107; 69.9%). Grade ≥ 3 peripheral neuropathy and nail disorders were uncommon. Conclusions: Cabazitaxel administration, in a real-world setting, is tolerated by Spanish patients with mCRPC, and the AEs are manageable.